2004
DOI: 10.1007/s00253-004-1821-1
|View full text |Cite
|
Sign up to set email alerts
|

Examination of fungal stress response genes using Saccharomyces cerevisiae as a model system: targeting genes affecting aflatoxin biosynthesis by Aspergillus flavus Link

Abstract: Saccharomyces cerevisiae served as a model fungal system to examine functional genomics of oxidative stress responses and reactions to test antioxidant compounds. Twenty-two strains of S. cerevisiae, including a broad spectrum of singular gene deletion mutants, were exposed to hydrogen peroxide (H2O2) to examine phenotypic response to oxidative stress. Responses of particular mutants treated with gallic, tannic or caffeic acids, or methyl gallate, during H2O2 exposure, indicated that these compounds alleviated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 25 publications
2
71
0
1
Order By: Relevance
“…This defence mechanism is a natural phenomenon that can be improved and controlled with different methods. For example the production of toxins can be modulated, as previously described, by the addition of antioxidants, which, in some cases, show also an intrinsic toxicity against pathogenic fungi (Fanelli et al, 1985(Fanelli et al, , 1986(Fanelli et al, , 2000Kim et al, 2004). As previously reported , comparable effects can be accomplished with compounds that protect the plant against oxidative stress.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This defence mechanism is a natural phenomenon that can be improved and controlled with different methods. For example the production of toxins can be modulated, as previously described, by the addition of antioxidants, which, in some cases, show also an intrinsic toxicity against pathogenic fungi (Fanelli et al, 1985(Fanelli et al, , 1986(Fanelli et al, , 2000Kim et al, 2004). As previously reported , comparable effects can be accomplished with compounds that protect the plant against oxidative stress.…”
Section: Discussionsupporting
confidence: 51%
“…These findings land basis for innovating biological approaches to control aflatoxin biosynthesis and fungal growth. Antimicrobials and antioxidants compounds such as thioproline, mannitol, α-and β-glucans, caffeic acid and derivatives, have been detected in these basidiomycetes and plants and might be of significance in modulating oxidative stress and aflatoxin formation (Kurashima et al, 1990;Kim et al, 2004). In A. parasiticus we have observed that the culture filtrates derived from some basidiomycetes affect transcription factors (such as Apyap1) regulating the expression of genes involved in the removal of reactive oxygen species (ROS), such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) enzymatic activities (Harschmann et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…14 The soil fungi used in this research included five strains of Aspergillus that differed from each other by their metabolite profiles and toxigenic potential: A. flavus NRRL 3357, a moderate producer of aflatoxins B 1 (7) and B 2 (8); A. flavus NRRL 29487, a high producer of aflatoxins B 1 and B 2 ; A. nomius NRRL 13137, a high producer of aflatoxins B 1 , B 2 , G 1 (9), and G 2 (10); A. parasiticus NRRL 29580, a very high producer of aflatoxins B 1 , B 2 , G 1 , and G 2 ; and A. parasiticus NRRL 29602, a producer of O-methyl sterigmatocystin (11). The data on the fungal toxigenic potentials (not listed here) were provided by Dr. B. Horn of the National Peanut Research Laboratory, ARS, USDA (Dawson, GA).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10 The action of caffeic acid 10 and other antioxidants tested (gallic and tannic acids and methyl gallate) was attributed to the alleviation of oxidative stress in fungi. 11 Treatment of A. flavus with resveratrol, 2 ( Figure 1), decreased aflatoxin production and the formation of conidia, the asexual spores of a fungus. In addition, this stilbenoid caused abnormal mycelial development and directly inhibited the expression of aflatoxin-biosyntheticpathway cluster genes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides the role in defense against UV, pathogens, parasites and predators, plant polyphenols have received special attention regarding their potent antioxidant properties which make them promising in suppressing oxidative stress associated disorders such as cancer. Inhibition of fungal growth and AF production by phenolics has been a subject of many studies (Hua et al, 1999;Kim et al, 2005Kim et al, , 2006RazzaghiAbyaneh et al, 2008). Hua et al (1999) showed that plant phenolics i.e.…”
Section: Plant-based Naturally Occurring Phenolicsmentioning
confidence: 99%